Contributions of Psychometrics to Studies in Cognitive Neuropsychology - Reppold, Caroline Tozzi (2015)
Although they have their own independent traditions, psychometrics and cognitive neuropsychology present various aspects that may be used in an interdisciplinary approach to widen knowledge in the psychology field. This paper aims to: 1. discuss how these two areas of knowledge might interact, 2. present contributions of psychometrics to studies in the field of cognitive neuropsychology, and 3. highlight advances in the field of cognitive neuropsychology using psychometric theories. This paper also discourses that neuropsychological assessment models are often based on convergent and criterion validity. However, new psychometrics trends point to the weakness of these models, and indicate the need for research related to the structure of scores, response processes, consequential validity, and, principally, the fit between theoretical models and their latent constructs. A reciprocal relation between psychometrics and cognitive neu ropsychology is important for the development of both these areas, as well as for psy cho logy in general.